Environmental Disclosure Practices Analysis on Companies Listed on the Indonesia Stock Exchange, Malaysia Exchange, and Thailand Stock Exchange - Nensi Febriani; Heri Yanto (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2020)
This study aims to determine differences in environmental disclosure practices in Indonesia, Malaysia, and Thailand and to identify factors that are suspected to influence environmental disclosure, including the size of the board of commissioners, profitability, and company size. The population of this study is large companies listed on the Bursa Efek Indonesia (BEI), the Bursa Malaysia (KLSE), and the Bursa Efek Thailand (SET) which are included in the largest stock market indexes in each exchange in 2018. The sampling method uses purposive sampling so that the research sample is 125 units of analysis. This study uses the One-Way ANOVA analysis and multiple regression analysis using the IBM SPSS 21 program. The results of the study indicate that there are no significant differences in environmental disclosure in Indonesia, Malaysia, and Thailand. The average level of environmental disclosure is 30.67% and included in the low category. The results of the multiple regression analysis showed that the size of the board of commissioners had a significant positive effect on environmental disclosure, while profitability and company size did not affect environmental disclosure.